Observation of temperature and pH during biogas production from water hyacinth and cow manure - Nurfitri Astuti; Tri Retnaningsih Soeprobowati; B Budiyono (Waste Technology, 2013)
Biogas is generated from biological process of organic material by bacterial engaged. Biogas can be derived from manure, municipal waste, agricultural waste and other biomass resources. In addition to the use of cow manure as raw material for biogas production, it can also be derived from biomass containing cellulose which one is water hyacinth as an organic material that contains quite large cellulose. The abundance of water hyacinth found in Rawapening causing several negative impacts. The purpose of this study is to observe  temperature and pH on the biogas production generated from water hyacinth of Rawapening and cow manure. Biogas production process begins by chopping the leaves and stems of water hyacinth, and then mixed with cow manure and water. The results of substrate variation of water hyacinth, cow manure and water reaches optimally at 40:80:480 respectively, which produce the highest point of  biogas amounted 176.33 ml on the day 20 in 1L sized digester, the temperature of the biogas production is at 32°C.  At the initial fermentation, digester temperature of 30°C has increased over the course of the fermentation process, a peak at day 20 and then decreased to 27°C at the end of fermentation. There is a decrease in pH starting from initial fermentation at pH 6-7 and then the pH began to decline until the end of fermentation as amount of pH 5.Doi: http://dx.doi.org/10.12777/wastech.1.1.22-25Citation:  Nurfitri Astuti, N., Tri Retnaningsih Soeprobowati, T.R., and  Budiyono. 2013. Observation of temperature and pH during biogas production from water hyacinth and cow manure. Waste Technology 1(1):1-5. Doi: http://dx.doi.org/10.12777/wastech.1.1.22-25